Does tougher enforcement make drugs more expensive?. (12th March 2014) - Pollack, Harold A.; Reuter, Peter
Abstract Aims To review empirical research that seeks to relate marginal increases in enforcement against the supply of illicit drugs to changes in drug prices at the level of the drug supply system being targeted. Method Review of empirical studies. Findings Although the fact of prohibition itself raises prices far above those likely to pertain in legal markets, there is little evidence that raising the risk of arrest, incarceration or seizure at different levels of the distribution system will raise prices at the targeted level, let alone retail prices. The number of studies available is small; they use a great variety of outcome and input measures and they all face substantial conceptual and empirical problems. Conclusion Given the high human and economic costs of stringent enforcement measures, particularly incarceration, the lack of evidence that tougher enforcement raises prices call into question the value, at the margin, of stringent supply‐side enforcement policies in high‐enforcement nations.